Pengaruh Kepemimpinan Transformasional Dan Keterlibatan Kerja Terhadap Komitmen Organisasi Pegawai Pada Bagian Kesejateraan Rakyat Sekretariat Daerah Kota Bima - Dila Saputri; Firmansyah Kusumayadi; Feni Aryani (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2025)
This study aims to determine the positive and significant impact of transformational leadership and work engagement on employee organizational commitment in the People's Welfare section of the Regional Secretariat of Bima City. The instrument in this study used a questionnaire with a Likert scale. The population in this study was 50 employees consisting of 35 Civil Servants, 2 Government Employees with Work Agreements, and 13 Regional Honorary Employees. The sample in this study was 35 civil servants with a sampling technique used, namely purposive sampling. Data collection techniques used observation, interviews, questionnaires, and documentation. Data analysis techniques used validity tests, reliability tests, multiple linear regression tests, classical assumption tests, correlation coefficient tests, determination coefficient tests, t tests, and f tests with the help of SPSS version 23 for Windows. The results of the study indicate that there is a positive and significant influence of transformational leadership and work engagement on employee organizational commitment in the People's Welfare section of the Regional Secretariat of Bima City.